Gambaran Pelaksanaan Performance Appraisal (PA) Di PT Pelindo Husada Citra - Munaa, Nihayatul; Khofifah, Rahayu Ainun; Kusdiyana, Ari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
Every job given to employees will be seen through employee performance. Basically employee performance is a result of work produced by an employee interpreted to achieve the expected goals. Of course, every company wants employees who have performance according to the standards set by the previous company or even exceed them. For this reason, an important activity of human resource management is needed, one of which is performance appraisal. Performance appraisal is needed to determine the results or level of success of employees. This study aims to describe the implementation of Performance Appraisal (PA) at PT Pelindo Husada Citra. This study uses a descriptive method by conducting interviews with key informants to see an overview of the implementation of Performance Appraisal (PA) at PT Pelindo Husada Citra. The results of this study show an overview of the implementation of Performance Appraisal at PT Pelindo Husada Citra when viewed from the management function, namely planning, organizing, actuating and controlling. PT Pelindo Husada Citra carried out Performance Appraisal (PA) activities well. If viewed from the management function, all criteria from the management function can describe the implementation of Performance Appraisal (PA) at PT Pelindo Husada Citra. This research is expected to be able to provide insight as material for management considerations for decision making in the process of implementing Performance Appraisal (PA).